PERFORMANCE EFFICIENCY ANALYSIS OF WATER TUBE BOILER MACHINE USING INPUT OUTPUT METHOD AND FMEA - Rahmat Hafis Ghifari; Nazaruddin; Muhammad Nur; Muhammad Isnaini Hadiyul Umam; Suherman (Indragiri Islamic University, 2025)
The objective of this study is to evaluate the efficiency of boiler machine performance at PT Wilmar Nabati Indonesia through the application of the Input-Output method and Failure Mode and Effect Analysis (FMEA). The input-output method is employed to calculate the efficiency of boiler performance, based on fuel consumption data and steam production flow. Meanwhile, FMEA was employed to identify and evaluate potential failures in various boiler equipment and to ascertain the severity, recurrence, and detection values associated with operational risks. The findings revealed a notable decline in boiler machine efficiency, with some days exhibiting values below the critical threshold of 76.22%. This decline is indicated by various factors, including poor fuel quality, temperature and pressure setting errors, and potential damage to boiler components. In order to address these issues, this study recommends a thorough audit of the boiler system, the implementation of stricter monitoring procedures, and the development of a boiler machine maintenance plan. With a better understanding of the factors affecting efficiency, it is hoped that the company can improve the performance of the boiler machine and prevent further damage.